# RUN: %kleaver --builder=constant-folding -print-ast %s > %t array a[64] : w32 -> w8 = symbolic # RUN: grep -A 2 \"# Query 1\" %t > %t2 # RUN: grep \"(query .. false)\" %t2 (query [] (Not (Ult (w32 0) (w32 1)))) # Check -- 0 + X ==> X # RUN: grep -A 2 \"# Query 2\" %t > %t2 # RUN: grep \"(query .. false .(Read w8 0 a).)\" %t2 (query [] false [(Add w8 0 (Read w8 0 a))]) # RUN: grep -A 2 \"# Query 3\" %t > %t2 # RUN: grep \"(query .. false .(Read w8 0 a).)\" %t2 (query [] false [(Add w8 (Read w8 0 a) 0)]) # Check -- C_0 + (C_1 + X) ==> (C_0 + C_1) + X # RUN: grep -A 2 \"# Query 4\" %t > %t2 # RUN: grep \"(query .. false .(Add w8 30 (Read w8 0 a)).)\" %t2 (query [] false [(Add w8 10 (Add w8 20 (Read w8 0 a)))]) # Check -- C_0 + (X + C_1) ==> (C_0 + C_1) + X # RUN: grep -A 2 \"# Query 5\" %t > %t2 # RUN: grep \"(query .. false .(Add w8 30 (Read w8 0 a)).)\" %t2 (query [] false [(Add w8 10 (Add w8 (Read w8 0 a) 20))]) # Check -- C_0 + (C_1 - X) ==> (C_0 + C_1) - X # RUN: grep -A 2 \"# Query 6\" %t > %t2 # RUN: grep \"(query .. false .(Sub w8 30 (Read w8 0 a)).)\" %t2 (query [] false [(Add w8 10 (Sub w8 20 (Read w8 0 a)))]) # Check -- C_0 + (X - C_1) ==> (C_0 - C_1) + X # RUN: grep -A 2 \"# Query 7\" %t > %t2 # RUN: grep \"(query .. false .(Add w8 246 (Read w8 0 a)).)\" %t2 (query [] false [(Add w8 10 (Sub w8 (Read w8 0 a) 20))]) # Check -- (X + Y) + Z ==> X + (Y + Z) # RUN: grep -A 3 \"# Query 8\" %t > %t2 # RUN: grep \"(query .. false .(Add w8 (Read w8 0 a)\" %t2 # RUN: grep \"(Add w8 (Read w8 1 a) (Read w8 2 a)\" %t2 (query [] false [(Add w8 (Add w8 (Read w8 0 a) (Read w8 1 a)) (Read w8 2 a))]) # Check -- (X - Y) + Z ==> X + (Z - Y) # RUN: grep -A 3 \"# Query 9\" %t > %t2 # RUN: grep \"(query .. false .(Add w8 (Read w8 0 a)\" %t2 # RUN: grep \"(Sub w8 (Read w8 2 a) (Read w8 1 a)\" %t2 (query [] false [(Add w8 (Sub w8 (Read w8 0 a) (Read w8 1 a)) (Read w8 2 a))]) # Check -- X + (C + Y) ==> C + (X + Y) # RUN: grep -A 3 \"# Query 10\" %t > %t2 # RUN: grep \"(query .. false .(Add w8 10\" %t2 # RUN: grep \"(Add w8 (Read w8 0 a) (Read w8 1 a)\" %t2 (query [] false [(Add w8 (Read w8 0 a) (Add w8 10 (Read w8 1 a)))]) # Check -- X + (Y + C) ==> C + (X + Y) # RUN: grep -A 3 \"# Query 11\" %t > %t2 # RUN: grep \"(query .. false .(Add w8 10\" %t2 # RUN: grep \"(Add w8 (Read w8 0 a) (Read w8 1 a)\" %t2 (query [] false [(Add w8 (Read w8 0 a) (Add w8 (Read w8 1 a) 10))]) # Check -- X + (C - Y) ==> C + (X - Y) # RUN: grep -A 3 \"# Query 12\" %t > %t2 # RUN: grep \"(query .. false .(Add w8 10\" %t2 # RUN: grep \"(Sub w8 (Read w8 0 a) (Read w8 1 a)\" %t2 (query [] false [(Add w8 (Read w8 0 a) (Sub w8 10 (Read w8 1 a)))]) # Check -- X + (Y - C) ==> -C + (X + Y) # RUN: grep -A 3 \"# Query 13\" %t > %t2 # RUN: grep \"(query .. false .(Add w8 246\" %t2 # RUN: grep \"(Add w8 (Read w8 0 a) (Read w8 1 a)\" %t2 (query [] false [(Add w8 (Read w8 0 a) (Sub w8 (Read w8 1 a) 10))])